2021
DOI: 10.1186/s12052-020-00141-9
|View full text |Cite
|
Sign up to set email alerts
|

Biology teachers’ conceptions of Humankind Origin across secular and religious countries: an international comparison

Abstract: Striving toward a better understanding of how the global spread of creationist ideology may impact biology teachers and teaching worldwide, this study comparatively examines how biology teachers from three Latin American countries (Argentina, Brazil, and Uruguay) conceive the origin of humankind. It is reported that teachers from Uruguay (the most secular country) and Argentina (a country with intermediate religiosity) more frequently associated humankind origin with scientific terms Evolution, Natural selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Hesitancy of teachers to teach evolution is not a phenomenon contained within the United States. To our knowledge, it has also been documented in Egypt (Mansour 2008), South Korea (Kim and Nehm 2011), Brazil, Argentina and Uruguay (Silva et al 2021), as well.…”
Section: Discussionmentioning
confidence: 62%
“…Hesitancy of teachers to teach evolution is not a phenomenon contained within the United States. To our knowledge, it has also been documented in Egypt (Mansour 2008), South Korea (Kim and Nehm 2011), Brazil, Argentina and Uruguay (Silva et al 2021), as well.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, it is relevant how teachers deal not only with student conceptions based on cognitive biases but also with religious and cultural concerns about evolution raised by their students (e.g., Scharmann & Grauer, 2020; Smith, 1994). However, this may be especially relevant for evolution education in other countries with a higher rate of students who reject evolution (e.g., Turkey; Köse, 2010) than is the case in Germany (Beniermann, 2019; Fenner, 2013; Konnemann et al, 2016; for a review, see Kuschmierz et al, 2020), since it has been shown that attitudes toward evolution are deeply rooted in the sociocultural and historical contexts of the countries of origin (Clément, 2015; Silva et al, 2021). Our purpose in this study, however, was to investigate how teachers diagnose and deal with cognitive biases that are common to students regardless of religious beliefs and worldview.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to measure evolution acceptance based on five clear statements related to the evolutionary theory: Earth age, the fossil record, common ancestry, and the origin of human beings. We included an item about understanding, related to deep time, as it has been considered a relevant barrier to evolution acceptance [ 59 ], while statements about human evolution are highly controversial even amongst biology teachers [ 60 ]. As mentioned before, the section of evolution provided scientific statements as a separated set of items as part of a longer questionnaire within the Relevance of Science Education (ROSE) project [see 56 ].…”
Section: Methodsmentioning
confidence: 99%